Operational images : from the visual to the invisual - Parikka, Jussi, 1976- (University of Minnesota Press, 2023)
"Serving as an extensive guide to a key concept in contemporary art, design, and media theory, Operational Images explores the implications of machine vision and the limits of human agency. Parikka considers the extent to which operational images have pervaded today's visual culture, outlining how data technologies continue to develop and disrupt our understanding of images beyond representation"--